Fact-Orientation and Conceptual Logic - Halpin, Terry (IEEE, 2011)
Fact-orientation is a conceptual approach to modeling information systems that captures the facts of interest in natural sentence structures without forcing some aspects to be modeled as attributes of other structures. Its graphical notation for data modeling enables a vast variety of business constraints to be depicted visually, while its formal basis in logic enables models to be transformed into implementation targets for execution. This paper provides a state-of-the-art overview of fact-orientation in general and second-generation Object-Role Modeling (ORM) in particular, highlighting its conceptual and visual support for logic-based modeling, and contrasting it with other data modeling approaches.